Influence of PCDH9 (rs9540720) and narcissistic personality traits on the incidence of major depressive disorder in Chinese first-year university students: findings from a 2-year cohort study - Xu, Ruixue; Liu, Zhaorui; Li, Hanyun; Luo, Linlin; Zheng, Yi; Mu, Fuqin; Liu, Yujia; Zhang, Weixin; Zhang, Ying; Wang, Jianli; Liu, Yan (Frontiers in Genetics, 2024)
Objective: To explore the influence of the polymorphism of the Protocadherin 9 (PCDH9) gene and narcissistic personality trait (NPT) on the risk of major depressive disorder (MDD) in Chinese first-year university students.A 2-year cohort study was conducted among Chinese first-year university students enrolled in 2018 from two universities in Shandong Province, China. The snapshot technique was used to detect the genotypes of PCDH9 (rs9540720). The Chinese version of the Composite International Diagnostic Interview was used for the MDD assessment. NPT was measured by 11 items based on DSM-IV. Patient Health Questionnaire-9 and Beck Anxiety Inventory were used to assess depressive and anxiety symptoms, respectively. Logistic regression modeling was carried out to examine the relationship between rs9540720, NPT, and the incidence of MDD.Results: 5,327 students participated in baseline and follow-up studies and provided blood samples. PCDH9 (rs9540720) (OR GG+GA =2.33, 95%CI: 1.35-4.02) and NPT (OR 5-9 =2.26, 95%CI: 1.40-3.64) increased the risk of MDD onset. There was no multiplicative interaction between NPT and Rs9540720 (OR=1.51, 95%CI: 0.30-7.63). Furthermore, there was no additive interaction between them (RERI=2.40, 95%CI: -0.82-5.62; AP=0.47, 95%CI: -0.04-0.97; S=2.37, 95%CI: 0.54-10.33).Conclusions: PCDH9 (rs9540720), and more NPTs are risk factors for the incidence of MDD in Chinese first-year university students.